Pengaruh Manajemen Keuangan dan Efikasi Diri Terhadap Intensi Berwirausaha Mahasiswa Prodi Manajemen Keuangan Syariah Universitas Islam Negeri Sulthan Thaha Saifuddin Jambi - Rendi Rostan; Titin Agustin Nengsih; Muhammad Ismail (Ekonomi Keuangan Syariah dan Akuntansi Pajak, 2024)
An entrepreneur must be perceptive and know how to seize opportunities. Business opportunities exist in all aspects of society and in all economic activities. Therefore, the key to spotting opportunities is creativity. The relationship between entrepreneurship, economic growth, and job creation is becoming increasingly relevant, as various studies indicate a positive correlation between entrepreneurship and economic growth. Ogunlana's study, cited from the setneg.go.id website, found that entrepreneurship can play a crucial role in achieving economic growth for countries to overcome economic crises. He asserts that entrepreneurship can generate jobs, foster innovation, increase production, and diversify sources of economic income by promoting the development of SMEs. This research aims to identify the factors influencing entrepreneurial intentions among students at the Faculty of Islamic Economics and Business at UIN STS Jambi. The results show that financial management significantly affects entrepreneurial intentions among students with a significance level of 0.001. Self-efficacy significantly affects entrepreneurial intentions among students with a significance level of 0.000. Simultaneously, it was found that financial management and self-efficacy together significantly affect entrepreneurial intentions with a significance level of 0.000.